2006
DOI: 10.1007/s00774-005-0674-8
|View full text |Cite
|
Sign up to set email alerts
|

The status of biochemical parameters in varying degrees of vitamin D deficiency

Abstract: Vitamin D (Vit D) is an essential element for the regulation of serum calcium, phosphate, and alkaline phosphatase (Alk Ph). Because the Vit D serum level is not usually measured directly, Vit D deficiency is diagnosed indirectly by changes in serum calcium, phosphate, and Alk Ph leves. The current study assessed the status of these biochemical parameters in subjects with different degrees of Vit D deficiency. We selected 1,210 subjects, between 20 and 69 years old, randomly from the Tehran population. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 21 publications
8
34
4
Order By: Relevance
“…It has been demonstrated that calcium, inorganic phosphate and alkaline phosphatase levels alone do not identify 25(OH)D depletion except when 25(OH)D is deficient (\25 nmol/L) [27], although our study does not entirely concur with this. We found a significant correlation between 25(OH)D and alkaline phosphatase, in that 15% of subjects in our study had elevated alkaline phosphatase concentrations and, of these, 57% had insufficient 25(OH)D. In general, patients with alkaline phosphatase concentrations greater than 120 IU/L, in the absence of liver or other bony diseases, are likely to have low 25(OH)D concentrations.…”
Section: Discussionsupporting
confidence: 67%
“…It has been demonstrated that calcium, inorganic phosphate and alkaline phosphatase levels alone do not identify 25(OH)D depletion except when 25(OH)D is deficient (\25 nmol/L) [27], although our study does not entirely concur with this. We found a significant correlation between 25(OH)D and alkaline phosphatase, in that 15% of subjects in our study had elevated alkaline phosphatase concentrations and, of these, 57% had insufficient 25(OH)D. In general, patients with alkaline phosphatase concentrations greater than 120 IU/L, in the absence of liver or other bony diseases, are likely to have low 25(OH)D concentrations.…”
Section: Discussionsupporting
confidence: 67%
“…Only four children had PTH levels above the normal reference values, two of them were infants and two were in the 2-5 years' group. These four children had 25OHD concentrations greater than 20 ng/ml and did not present clinical or biochemical data of secondary hyperparathyroidism [42].…”
Section: Discussionmentioning
confidence: 96%
“…Vitamin D level ≤12.5 nmols/l was classified as severe vitamin D deficiency, 12.5-25 nmols/l was classified as moderate Vitamin deficiency and >25 nmols/l was classified as mild vitamin D deficiency. 16 After measuring the height in cm and weight in kg, Body Mass Index (BMI) was calculated. The weight was measured with light clothing and no shoes.…”
Section: Methodsmentioning
confidence: 99%